PENINGKATAN KETRAMPILAN HIDUP KOMUNITAS DIFABEL MELALUI PELATIHAN PEMBUATAN KUE KERING - Aditya Rahman; Sahbudin Amir; Nurul Aliah Fil Hafirah; Fadhlur Sani; Yuliana Yuliana; Koch Asiye Melek; Nafida Hetty Marhaeni (Gapenas Publisher, 2023)
Cookies is a dense textured cake, durable, and has many enthusiasts. The easy making of cookies can be followed by all people, including people with disabilities. Therefore, the purpose of this service is an effort to improve the life skills of persons with disabilities through training for making cookies. This dedication was carried out at the Difabel Pinilih Sedayu Family Forum located in Bantul, Yogyakarta Indonesia. Training conducted every Saturday during the service team conducted a community service (KKN) using an active participation approach, activities orientation approach, program approach, and independence approach so that the objectives of service are achieved. The stages undertaken to conduct this training are preparation and implementation. At the preparation stage, the team conducted a trial to obtain the best cookie recipes that can be followed by persons with disabilities, preparation for materials, preparation of tools, and preparation for training. After everything is prepared, it is followed by training in making cookies by the devotion team. The training results show that when the implementation of all the disabled friends who were invited were present, during the manufacturing process all were actively involved, and the results of cookies were liked by disabled friends. This makes the training objective achieved, namely disabled people can have the skills to make cookies